ANALYSIS OF THE RELATIONSHIP BETWEEN HIGHER ORDER THINKING SKILLS AND SCIENTIFIC REASONING SKILLS IN CHEMISTRY LEARNING - Sofianto, Eko Wahyu Nur; irawati, Ratna Kartika (NUKLEO SAINS : JURNAL PENDIDIKAN IPA, 2026)
Higher Order Thinking Skills (HOTS) and Scientific Reasoning Skills (SRS) play a significant role in helping students develop a comprehensive understanding of chemistry concepts. However, studies examining the relationship between HOTS and SRS remain limited. Such studies are essential for providing a theoretical foundation for the development of chemistry instruction in schools. Therefore, this study aims to analyze the relationship between HOTS and SRS in chemistry learning. This study employed a narrative literature review approach, with HOTS and SRS as the focus of the review. Relevant literature was identified through the Google Scholar database, covering publications from 2020 to 2026, using the keywords "higher order thinking skills" OR "scientific reasoning skills" AND "chemistry learning." A total of 27 relevant articles were selected for analysis. The data were analyzed by synthesizing and presenting the findings of previous studies in a narrative and descriptive manner. The review revealed that scientific reasoning skills constitute an essential component of HOTS that students need to develop a meaningful and comprehensive understanding of chemistry concepts. Furthermore, the dimensions of scientific reasoning contribute to the development of students' HOTS, thereby supporting the acquisition of essential twenty-first-century skills.